The effect of endurance exercise modality on markers of fatigue - Moorea, A. R.; Hutchinsona, J. C.; Wintera, C. R.; Daltona, P. C.; Paolonea, V. J. (International Journal of Kinesiology & Sports Science, 2021)
Background: Exercise power output, and resulting fatigue, is regulated based on central and peripheral sensory input. Whether exercise mode, specifically, contributes to this regulation remains unexplored. Objective: This study was designed to determine if differences in markers of fatigue would be present during two time trials of similar duration and intensity, as a result of exercise mode (cycling and rowing). Method: In a randomized crossover design, nine subjects completed the two 7-min time trials, on different days. Exercise power output, heart rate, rating of perceived exertion, and blood lactate measurements were analyzed using repeated-measures ANOVAs. Results: There was a significant interaction between mode and time for power output (p =.02), but no significant differences between matched time points were observed for any of the dependent variables used to assess fatigue (p >.05). Conclusion: Similar levels of heart rate, perceived exertion, and blood lactate for time trials on different modes, but with the same duration and directed intensity, suggest that in a laboratory environment, exercise is regulated more by physiological disturbance and sensory cues than by exercise mode. These findings support the sensory tolerance limit of exercise fatigue.